Efeitos de Anacardium occidentale L. na sepse de camundongos diabéticos - OLIVEIRA, Aluisio da Silva (2018)
Sepsis is defined by the presence of organic dysfunction resulting from infection and generalized inflammation, with high mortality rates, especially among diabetic patients. For this reason, the objective of the present study was to evaluate the effect of the ethanol extract of the flowers of Anacardium occidentale L. in an experimental model of sepsis in diabetic mice. Five-month-old male Swiss mice were used. Diabetes was induced by ad libitum intake of 40% fructose, added to water, for 21 days. On day 14 animals received Streptozotocin (40 mg / kg ip.). Animals with glucose > 200mg / dL were considered diabetic. To determine survival, sepsis by cecal puncture was induced in diabetic animals, which were divided into the following groups (N = 5): Control: received saline; ATB: treated with Imipenem (8mg / kg), subcutaneously (sc) at the time of induction of sepsis and oral EEA: 5mg / kg of Ethanol Extract from Anacardium occidentale, orally, during sepsis. The remaining animals (N = 7 / group), following the same division of the previous groups, were euthanized to evaluate EEA efficacy considering: cell migration; peritoneal inflammatory exudate; cellularity; (H2O2), Nitric Oxide (NO) and cytokine production IL-6, IL-10, MCP-1, INF-y, TNF-α and IL-12. The association with fructose and streptozotocin induced diabetes in Swiss mice. The extract of the flowers of Anacardium occidentale increased the survival of diabetic mice at the time of sepsis but did not prolong it for a long time. On the other hand, it reduced the bacterial infection in the blood, but it was not effective in controlling the bacterial growth in the peritoneum and lung, however, it acted in the balance between inflammatory mediators, increasing the production of hydrogen peroxide and reducing the production of nitric oxide, in addition, it proved to be efficient in controlling exacerbated systemic inflammation in sepsis, by reducing pro-inflammatory cytokines such as IL- 6, TNF-α and the chemokine MCP-1. We conclude that the treatment offered presents promising results regarding the action of Anacardium occidentale on sepsis induced in diabetic mice.